Parenting stress and preschoolers' socio-emotional adjustment: the mediating role of parenting styles in parent–child dyads. Issue 4 (1st October 2020) - Carapito, Elsa; Ribeiro, Maria Teresa; Pereira, Ana Isabel; Roberto, Magda Sofia
ABSTRACT: This study examined the mediating effect of parenting styles in the relationship between parenting stress and children's socio-emotional adjustment through Structural Equation Modeling. The moderating role of parent and child gender was also examined by means of a multi-group analysis. A sample of 552 mothers and 501 fathers of Portuguese families with preschoolers participated in the study. Mothers and fathers independently completed self-report measures to evaluate parenting stress, parenting styles and the child's socio-emotional adjustment (children's social skills, internalizing and externalizing behavioral problems). Results regarding direct effects indicated that mothers' and fathers' stress contributed to the child's social skills. Additionally, results showed indirect effects: fathers' authoritative parenting mediated the link between fathers' stress and social skills, regardless of the gender of the child, while for mothers, the corresponding mediation effect was only observed for daughters; fathers' authoritarian parenting mediated daughters' externalizing problems while fathers' permissive parenting mediated daughters' internalizing problems. Overall, this study emphasizes the importance of both parents for the adjustment of their children, in addition to the need to examine dyadic parent–preschooler relationships, given that the results suggest some specificity in the processes responsible for direct and indirect effects.